Comparative evaluation of maternal and neonatal outcomes using the WHO labour care guide versus the WHO-modified partograph: a prospective observational study - Singh, Kumari Anjali; Singhal, Sunita; Sharma, Rupali; Khan, Iftesham (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Labour and childbirth remain critical phases in maternal care, with significant implications for maternal and neonatal outcomes. Despite declining global mortality rates, disparities persist, particularly in low-resource settings. Effective labour monitoring tools are essential for improving outcomes and reducing complications. This study aimed to compare maternal and neonatal outcomes using the WHO Labour Care Guide (LCG) versus the WHO-Modified Partograph (WHO-MP) for intrapartum monitoring. Methods: This prospective observational study was conducted at GS Medical College & Hospital over 15-18 months. A total of 200 full-term pregnant women in active labour (≥4 cm cervical dilation) were randomly assigned to either the WHO-LCG group (n=100) or the WHO-MP group (n=100). Inclusion criteria encompassed singleton pregnancies with vertex presentation and no medical or obstetric complications. Labour progression, delivery mode, maternal complications, and neonatal outcomes were recorded and analysed using SPSS v27. Results: Normal vaginal deliveries were higher in the LCG group (86%) compared to WHO-MP (78%), with lower maternal infection rates (6% vs. 18%, p=0.005) and postpartum hemorrhage (1% vs. 6%). The LCG group showed significantly shorter labour durations and NICU stays. Apgar scores and NICU admission rates were comparable, though early neonatal recovery was more favorable in the LCG group. Conclusions: The WHO Labour Care Guide provides a structured, patient-centered approach to labour monitoring, potentially enhancing maternal and neonatal outcomes through timely and individualized care.